Kicking power - Haines, T. L.; Erickson, T. M.; McBride, J. M. (Strength and Conditioning Journal, 2012)
Kicking is an integral maneuver in many team sports. There are different types of kicks such as the instep kick, side-foot kick, and drop-punt kick. By examining the different segments of a kick, one can determine the properties that allow for optimal performance. The basic tenants of kicking performance involve angular velocity of the hip generated through a stretch-shortening cycle and the linear velocity of the foot in combination with the force applied to the ball, which determines kicking power. The strength and conditioning professional can use this information to design a training program that optimizes kicking performance.